Sustainable agriculture strategy: analysis of macroarthropods diversity in cabbage farming systems - Nasik, Isman; Tarwotjo, Udi; Hadi, Mochamad; Mubarok, Rizal Husni (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2025)
Cabbage is a widely consumed vegetable in Indonesia, but the role of soil macroarthropods in cabbage cultivation is often overlooked by farmers. This study aimed to analyze the structure of soil macroarthropod communities and the abiotic factors influencing them in monoculture and polyculture cabbage fields. The research was conducted in Batur Village, Getasan, Central Java, on three types of land: cabbage monoculture, cabbage polyculture, and forest as a control. Samples were collected using the pitfall trap method and identified at the Ecology and Biosystematics Laboratory. The highest diversity index was found in polyculture fields (H′ = 1.02), followed by monoculture (H′ = 0.85) and forest (H′ = 0.19). The evenness index was also highest in polyculture fields (E = 0.69). The Formicidae family dominated all three land types, with a community similarity index of 44% between monoculture and polyculture fields. Statistical tests showed significant differences between the forest and agricultural lands (p < 0.05), but no significant difference between monoculture and polyculture systems (p > 0.05). Correlation analysis revealed that soil moisture had a strong positive correlation with diversity and evenness, while temperature showed a negative correlation with those indices. These findings indicate that although polyculture tends to support higher diversity, the difference was not statistically significant. This information is expected to encourage more adaptive and sustainable farming practices while maintaining biodiversity in agricultural lands.